Managing gestational diabetes mellitus using a smartphone application with artificial intelligence (SineDie) during the COVID-19 pandemic: Much more than just telemedicine. (November 2020) - Albert, Lara; Capel, Ismael; García-Sáez, Gema; Martín-Redondo, Pablo; Hernando, M. Elena; Rigla, Mercedes
Highlights: Gestational diabetes mellitus is a disease that requires frequent hospital visits. The current COVID-19 pandemic has brought telemedicine in the spotlight. Decision support tools integrated into telemedicine systems can help clinicians. SineDie© app analyses the data and makes recommendations regarding diet or insulin. SineDie© app may be an excellent tool for GDM remote management. Abstract: We describe our experience in the remote management of women with gestational diabetes mellitus during the COVID-19 pandemic. We used a mobile phone application with artificial intelligence that automatically classifies and analyses the data (ketonuria, diet transgressions, and blood glucose values), making adjustment recommendations regarding the diet or insulin treatment.